1997
DOI: 10.1016/s0741-5214(97)70035-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after early infrainguinal graft failure

Abstract: The long-term limb salvage and graft patency rates after takeback revascularization procedures for early graft failure are poor. Despite poor outcome, a single takeback procedure appears warranted in all patients. Multiple takeback procedures, however, do not appear to be justified, especially in patients who are given anticoagulation medication after the index bypass procedure, repeat leg bypass procedures, or if there is no potential for graft revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The intervention for tissue loss may be explained by 2 factors: delayed recognition of ischemia and due to the higher incidence of diabetes and thus neuropathy in this group. 2 This had previously been demonstrated 2,[14][15][16] in AAs where tissue loss and critical ischemia were more likely in AAs in up to 90%; while in the CAs, it was up to 80%. However, Rowe et al did not find any difference in the indication for surgery in their cohort.…”
Section: Indication For Surgerymentioning
confidence: 74%
“…The intervention for tissue loss may be explained by 2 factors: delayed recognition of ischemia and due to the higher incidence of diabetes and thus neuropathy in this group. 2 This had previously been demonstrated 2,[14][15][16] in AAs where tissue loss and critical ischemia were more likely in AAs in up to 90%; while in the CAs, it was up to 80%. However, Rowe et al did not find any difference in the indication for surgery in their cohort.…”
Section: Indication For Surgerymentioning
confidence: 74%
“…5,19 It is associated with significantly decreased graft patency and increased risk of major complications, including reoperation, major amputation, and death. [20][21][22] Avoidance of early graft failure has led some surgeons to perform CIM, including arteriography and duplex ultrasound, to ensure technical adequacy of LEB. [5][6][7][8]10,11,16,19 Multiple studies have demonstrated excellent results in infrainguinal LEB performed with either routine completion angiography 7,16 or duplex ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A failed infrainguinal bypass is associated with poor prognosis for the limb in question, particularly if the graft was initially placed for limb salvage. [1][2][3] This concern regarding patency has led many investigators to identify characteristics associated with infrainguinal bypass failure, leading to the recommendations of increased surveillance and preemptive interventions on vein grafts. 4,5 Graft failures are traditionally grouped into early and late.…”
mentioning
confidence: 99%